2019
DOI: 10.1097/hs9.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

AXL Inhibition Extinguishes Primitive JAK2 Mutated Myeloproliferative Neoplasm Progenitor Cells

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to show high levels of activated AXL in untreated MPN patients compared with healthy donors. This finding confirms previously published data by Pearson et al 27 describing upregulation and activation of AXL in primary cells isolated from JAK2-mutated pre-treated MPN patients. We furthermore showed that genetic knockdown, as well as pharmacologic blockade of AXL using bemcentinib, inhibit proliferation and induce apoptosis of JAK2V617F + cell lines.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, this study is the first to show high levels of activated AXL in untreated MPN patients compared with healthy donors. This finding confirms previously published data by Pearson et al 27 describing upregulation and activation of AXL in primary cells isolated from JAK2-mutated pre-treated MPN patients. We furthermore showed that genetic knockdown, as well as pharmacologic blockade of AXL using bemcentinib, inhibit proliferation and induce apoptosis of JAK2V617F + cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found significant higher GAS6 levels in BM plasma of MPN patients in comparison to healthy individuals suggesting that there might be a similar interaction of MPN cells with mesenchymal stem cells resulting in induction of GAS6 secretion by stromal cells. Our study confirms previous findings 27 that levels of GAS6 in PB plasma are not increased in the whole cohort of MPN patients. However, we found that PB GAS6 levels were increased in the subgroup of MF patients only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been demonstrated that AXL is associated with CML resistance, and its inhibitory effect has therapeutic potential in BCR/ABL-resistant CML [ 38 ]. Moreover, Pearson et al reported that inhibiting AXL may be a new therapeutic target for JAK2-induced MPNs [ 39 ]. CA induced the glioblastoma cell apoptosis through inhibition of STAT3 and NF-κB activation and induction of apoptotic-related caspases pathways.…”
Section: Discussionmentioning
confidence: 99%
“…After 3 hours incubation with the WST-1 reagent absorbance was measured at 450nm on a 800TS microplate reader (BioTek). Colony forming assays on primary patient samples were performed in methylcellulose complete media (R&D systems) supplemented with 2u/ml EPO with CD34 + cells at a density of 3000cells/ml as previously described [ 22 ]. To assess retention of self-renewal capacity the resulting colonies at day 7 were replated in methylcellulose in the absence of any drugs and colonies counted at 14 days.…”
Section: Methodsmentioning
confidence: 99%